2017
DOI: 10.1155/2017/5091027
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Selank Enhances the Effect of Diazepam in Reducing Anxiety in Unpredictable Chronic Mild Stress Conditions in Rats

Abstract: It was shown that the anxiolytic effect of Selank is comparable to that of classical benzodiazepine drugs and that the basis of their mechanism of action may be similar. These data suggest that the presence of Selank may change the action of classical benzodiazepine drugs. To test this hypothesis, we evaluated the anxiolytic activity of Selank and diazepam in rats both under conditions of unpredictable chronic mild stress and in its absence, after the individual and combined administration of these compounds u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In an attempt to better position their ostensible stress hyporesponsiveness in its relevant (patho)physiological context (i.e., resilience as opposed to cognitive-emotional deficit), we exposed Ahi1+/− mice to a protocol of chronic unpredictable stress (CUS) that consisted of various psychological stressors administered in random order over a period of 9 weeks. CUS paradigms are based on the chronic, mild stress protocol of Willner et al 20 that has been shown to induce anhedonia (e.g., 21 , 22 ) along with decreased hippocampal neurogenesis 23 , 24 . With respect to anxiety, data are less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to better position their ostensible stress hyporesponsiveness in its relevant (patho)physiological context (i.e., resilience as opposed to cognitive-emotional deficit), we exposed Ahi1+/− mice to a protocol of chronic unpredictable stress (CUS) that consisted of various psychological stressors administered in random order over a period of 9 weeks. CUS paradigms are based on the chronic, mild stress protocol of Willner et al 20 that has been shown to induce anhedonia (e.g., 21 , 22 ) along with decreased hippocampal neurogenesis 23 , 24 . With respect to anxiety, data are less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Following administration of selank and GABA in frontal cortex nerve cells of rats, similar gene expressions occurred, and selank further increased activity of inhibitory neurons reliant on GABA 115,116 . Due to these peptide modulation abilities, exposure to selank is thought to influence binding of GABA to GABA A receptors 117 . This unique mechanism has been hypothesized to cause pronounced anxiolytic, antidepressant, and antiaggression effects.…”
Section: Treatment Considerationsmentioning
confidence: 94%
“…A similar effect was also attributed to Semax, another synthetic heptapeptide, consisting of a fragment of adrenocorticotropic hormone (ACTH4–7) C‐terminally fused to the tripeptide PGP. Additionally, immunomodulatory and neuropsychotropic effects have also been ascribed to these molecules . Currently and to the best of our knowledge, no clinical studies with these peptides have been terminated or were given a positive advice by the European Medicines Agency.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immunomodulatory and neuropsychotropic effects have also been ascribed to these molecules. 7,10,11 Currently and to the best of our knowledge, no clinical studies with these peptides have been terminated or were given a positive advice by the European Medicines Agency. Therefore, the use of these research peptides on humans has not been approved by the European Union and can therefore be considered illegal.…”
mentioning
confidence: 99%